Conhecimento e opinião da população sobre o transplante e a doação dos tecidos da face - Rossetto, Daniela Cristina Pavan [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The face transplantation is a surgical procedure in which facial structures are transplanted from one person to another. It's a complex procedure on a medical point of view, moral and psychological, therefore provides many benefits in terms of improving aesthetic function and social integration. To evaluate the knowledge and opinion of the population about the donation and transplantation of facial tissues. From August 2011 to October 2012 a questionnaire was administered to 430 people, randomly selected, with twenty-one years of age or older, systematically collected in all regions (north, south, center , east and west) of the city of Botucatu, state of São Paulo. The study of the objective responses of all participants in the different issues was accomplished by establishing a frequential distribution data presented using tables and graphs and analyzed by chi square (à) for a sample. The analysis of the responses were discussed at the 5% level of significance and considered significant when the p value was <0.05, showing that the distribution is not uniform, but uniformly distributed of the classes. The answers to the descriptive questions were analyzed by reading them and preparation of a summary with analysis by region. Of the participants, 65.8% did not have any knowledge about facial tissue donation, 90.1% knows that face transplantation is indicated in cases of facial deformities, 51.7% are able to donate tissues of the face, 67.7% are not aware how their families would react against its manifestation in life to give tissues of the face, 84% have no knowledge about the implications on the funeral ceremonies. Of all participants, 359 would accept to live with other face if necessary and 375 would support any family members in being a donor. The population showed a limited knowledge about the implications on the donation and transplantation of face tissues, but would accept to live with if necessary and support any family members ...

O transplante de face é um procedimento cirúrgico no qual as estruturas da face de uma pessoa são transplantadas para outra. É uma cirurgia ousada do ponto de vista médico, moral e psicológico, pois, proporciona enorme benefício em termos de melhora da função estética e integração social. Avaliar o conhecimento e a opinião da população sobre o transplante e a doação dos tecidos da face. No período de agosto de 2011 a outubro de 2012 foi aplicado um questionário a 430 pessoas, escolhidas aleatoriamente, na faixa etária acima de vinte e um anos de idade, numa sistemática de coleta seguida em todas as regiões (norte, sul, centro, leste e oeste) da cidade de Botucatu, interior do Estado de São Paulo. O estudo das respostas dos participantes nas diferentes questões objetivas apresentadas foi realizado estabelecendo-se a distribuição frequencial dos dados apresentada por meio de tabelas ou gráficos e analisadas pelo teste do Qui quadrado ( א) para uma amostra. A análise das respostas obtidas foram discutidas ao nível de 5% de significância e consideradas significativas quando o valor de p foi < 0,05, mostrando que a distribuição não é uniforme, mas uma distribuição uniforme das classes. Nas questões dissertativas a análise foi realizada a partir da leitura das mesmas, com elaboração de um resumo das respostas e análise preferencial por região. Dos participantes, 65,8% não possuem conhecimento a respeito da doação dos tecidos da face; 90,1% têm conhecimento que o transplante de face está indicado nos casos de deformidades faciais; 51,7% doariam a face; 67,7% não saberiam como seus familiares reagiriam frente a sua manifestação em vida de doar os tecidos da face; 84% não sabem as implicações sobre as cerimônias fúnebres. Dos participantes, 359 aceitariam conviver com outra face caso fosse necessário e 375 apoiariam se algum familiar manifestasse vontade em ser um doador. A população demonstrou ...
Keywords: Transplante de orgãos, tecidos, etc; Doação de órgãos, tecidos, etc; Pele - Enxerto; Face - Cirurgia; Saúde pública - Pesquisa; Donation of organs, tissues, etc